A Study on the Impact of Most Commonly used Pesticides on Growth and Biochemical Parameters of Some Species of Cyanobacteria: Impacts of commonly used pesticides on Cyanobacteria growth and metal stress effects (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The goal is to investigate the effects of common pesticides on the growth and biochemicalparameters of some Cyanobacteria species, isolate, purify, and identify cyanobacterial strains, growthkinetics of purified samples, and biochemical parameters under selected metal stress, as well as thefrequency of heterocyst and akinete under control and treated conditions. The Subarnarekha Riverbasin, which runs through Ranchi district in India's Jharkhand state, served as the study area. PASWSPSS-18 was used to calculate one way ANOVA and multiple co-relations to investigate the probabilitydistribution pattern and significance of the collected data. Higher amounts of MDA accumulation undertreatment conditions might be the consequence of photosynthetic membrane rupture, which causes abrief rise in SOD activity in the test organism. MDA An increase in SOD activity might be used as abiomarker for metal exposure. When Nostoc carneum blooms in water, it provides more surface area forthe metal binding abilities of the other two species, potentially making it a highly effective heavy metalremoval agent. Furthermore, it is cost-effective, ecologically friendly, and can be mass-produced.